The development of an Iron Age and Roman settlement complex at The Park and Bowsings, near Guiting Power, Gloucestershire : farmstead and stronghold - Marshall, Alistair (Archaeopress Archaeology, 2020)
Excavations near Guiting Power in the Cotswolds reveal evidence of occupation until the late 4th century AD: a relatively undefended middle Iron Age farmstead was abandoned, followed by a mid to later Iron Age ditched enclosure. This latter site perhaps became dilapidated, with a Romanised farmstead developing over the traditional habitation area